2022
DOI: 10.1038/s41598-022-25192-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel pectin-based nanocomposite film for active food packaging applications

Abstract: Novel pectin-based films reinforced with crystalline nanocellulose (CNC) and activated with zinc oxide nanoparticles (ZnO NPs) were prepared by solvent-casting method. Film ingredients enhanced UV-blocking, thermal, and antibacterial properties of active films against well-known foodborne pathogens. Optimal active films exhibited higher mechanical, water vapor barrier properties compared to pristine pectin films. SEM confirmed the even distribution of CNC and ZnO NPs in pectin matrix and their interactions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The authors also reported the maintenance of the initial reddish color and a reduction in the oxidation process when compared to unwrapped meat [24]. In the recent work by Sharaby et al [52], composite films of pectin/ZnONP/CNC (cellulose nanocrystals) were evaluated in the preservation of sliced cheese after contamination with Staphylococcus aureus. The samples protected in the active films presented reductions of up to 1.2 log CFU/g after 5 days in refrigerated conditions (7 • C), and the small antimicrobial activity of the films was attributed to the small release of Zn 2+ to the cheese [52].…”
Section: Microbiological Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors also reported the maintenance of the initial reddish color and a reduction in the oxidation process when compared to unwrapped meat [24]. In the recent work by Sharaby et al [52], composite films of pectin/ZnONP/CNC (cellulose nanocrystals) were evaluated in the preservation of sliced cheese after contamination with Staphylococcus aureus. The samples protected in the active films presented reductions of up to 1.2 log CFU/g after 5 days in refrigerated conditions (7 • C), and the small antimicrobial activity of the films was attributed to the small release of Zn 2+ to the cheese [52].…”
Section: Microbiological Growthmentioning
confidence: 97%
“…In the recent work by Sharaby et al [52], composite films of pectin/ZnONP/CNC (cellulose nanocrystals) were evaluated in the preservation of sliced cheese after contamination with Staphylococcus aureus. The samples protected in the active films presented reductions of up to 1.2 log CFU/g after 5 days in refrigerated conditions (7 • C), and the small antimicrobial activity of the films was attributed to the small release of Zn 2+ to the cheese [52]. Another shelf-life assessment of fresh poultry meat protection in active films incorporated with ZnO NPs was conducted by Mohammadi et al [53].…”
Section: Microbiological Growthmentioning
confidence: 99%
“…The films exhibited increased mechanical, thermal and barrier properties compared with native pectin films. 97…”
Section: Zinc Oxide Nanoparticles (Zno Nps)mentioning
confidence: 99%
“…Cheese samples wrapped with the developed films stored at 7°C for 5 days significantly reduced the total population counts by at least 1.02 log CFU/g. The films exhibited increased mechanical, thermal and barrier properties compared with native pectin films 97 …”
Section: Pectin‐based Active Food Packaging Filmsmentioning
confidence: 99%
“…6 Recently, research interests have been growing toward the development of biodegradable and sustainable packaging material that can increase the shelf life of packaged food. 7 These demands inspired to develop active food packaging films, which can prevent the deterioration of food products by microbial contamination, off-flavor development, oxidation, texture breakdown, and can provide efficient moisture and gasbarrier properties. 8 Biopolymers have been used in making active packaging materials as they are renewable, abundant in nature, low cost, ecofriendly, and biodegradable.…”
Section: Introductionmentioning
confidence: 99%